2020
DOI: 10.46483/deuhfed.669779
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklar İçin Yeme Davranışları Ölçeğinin Türkçe Geçerlik ve Güvenirliği

Abstract: Yeme davranışı, yemek yeme ve yeme zamanını içeren biyopsikososyal kökenli karmaşık bir davranıştır. Amaç: Bu çalışma, engelli çocuğa sahip aileler tarafından değerlendirilen Çocuklar İçin Yeme Davranışları Ölçeği'nin (The Children's Eating Behavior Inventory/CEBI) Türkçe eşdeğerliğini sağlamak, geçerlik ve güvenirliğini belirlemek amacı ile yapılmıştır. Yöntem: Ölçek için çeviri geri çeviri yöntemi, içerik geçerliği için kapsam geçerlik indeksi, yapı geçerliği için açıklayıcı ve doğrulayıcı faktör analizi yap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Reliability coefficients were determined as .75 for the fate subscale, .90 for the susceptibility/severity subscale, and .66 for the preventability subscale. High scores obtained from each subscale showed that children had a positive attitude towards playground accidents (21). Cronbach's alpha value of the scale in this study is .63 for the fate subscale, .55 for the susceptibility/severity subscale, and .61 for the preventability subscale.…”
Section: The Injury Attitudes Questionnaire For School Children (Iaq)mentioning
confidence: 50%
See 2 more Smart Citations
“…Reliability coefficients were determined as .75 for the fate subscale, .90 for the susceptibility/severity subscale, and .66 for the preventability subscale. High scores obtained from each subscale showed that children had a positive attitude towards playground accidents (21). Cronbach's alpha value of the scale in this study is .63 for the fate subscale, .55 for the susceptibility/severity subscale, and .61 for the preventability subscale.…”
Section: The Injury Attitudes Questionnaire For School Children (Iaq)mentioning
confidence: 50%
“…The elementary education institutions in Turkey involved the four-year compulsory primary school level (1 st , 2 nd , 3 rd , and 4 th grades) and the four-year compulsory middle school level (5 th , 6 th , 7 th, and 8 th grades) (20). In addition, the Turkish validity and reliability study of the Injury Attitudes Questionnaire for School Children (IAQ) used in the present study was conducted with children aged between 8 and 12 (21). For this reason, 3 rd and 4 th -grade students in primary school were included in this study so that the results would not differ in terms of the level of education.…”
Section: Arkan-uner G Et Al Schoolchildren's Attitudes Injurymentioning
confidence: 99%
See 1 more Smart Citation